South Pacific Ocean (London, 1885)
Kartta kuuluu A. E. Nordenskiöldin kokoelmaan Small corrections 1874, 1878, 1884, large corrections Jan. 1885 Sketch of the Auckland Islands Campbell Island Auckland Islands : Port Ross or Sarah's Bosom Harbour Campbell Island : South or Perseverance Harbour Hanfield inlet Carnley Harbour, Camp Cove